Psilocybe ningshanensis (Hymenogastraceae, Agaricales), a new species from China - He, Xue-Lian; Huo, Wen-Yan; Zhang, Li-Guang; Liu, Yu; Qi, Peng; Dai, Lu; Qiao, Ting; Lu, Pengpeng; Li, Jun-Zhi (Phytotaxa, 2022)
The Qinling Mountains are the geographic boundary between northern and southern China. In our current study, we investigated the biodiversity of macrofungi in the Qinling Mountains of Shaanxi and discovered a new species, Psilocybe ningshanensis. The phylogenetic tree shows its position in a group composed by P. hopii and P. mescaleroensis. They differ in some macro- and microscopic features, such as the presence or absence of an annulus or veil, the surface characteristics of the pileus, and the sizes and shapes of basidiospores and cheilocystidia. In addition, they are geographically distanced. P. ningshanensis was first discovered in Ningshan, China, whereas P. hopii and P. mescaleroensis were both found in the United States. In this article, we introduce the new species with illustrated description, ITS sequences, and comparisons with similar species.